PENGARUH MOTIVASI, PEMANFAATAN TEKNOLOGI INFORMASI, SANKSI ADMINISTRASI DAN TINGKAT PENDAPATAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR - Sri Lestari Yuli Prastyatini; Yunita Adi Nabela (ITB AAS INDONESIA, 2023)
This research aims to determine the effect of motivation, utilization of information technology, administrative sanctions, and income levels on motor vehicle taxpayer compliance. Source of date used in this research is primary data. The population used is motorvehicle taxpayers in Kapanewon Wonosari, Gunungkidul Regency. The sample in this research were 115 motor vehicle taxpayers in sampling. Analysis of the data used using multiple linear analysis. The results showed that motivation and utilization of information technology had no effect on motor vehicle tax compliancewith significant values of 0.387 and 0,052. Administrative sanctions and income levels have a positive effect on motor vehicle taxpayer compliance with significant values of 0.000 and 0.000 respectively and t values of 3.632 and 5.303 respectively.